Perencanaan Kebutuhan Air Bersih pada Gedung Workshop E I dan E II Kampus Teaching Industry Politeknik Negeri Sriwijaya - Amalia, Kiki Rizky; Sari, Anggi Nidya; Sakri, Harfa (Jurnal Talenta Sipil, 2024)
Clean water is a need for every living creature. Clean water is water that physically looks clear and has no smell that is used for daily purposes and can be cooked to make drinking water. In carrying out daily activities, humans need clean water. One of them is in teaching and learning activities at an institution. To ensure comfort in the teaching and learning process, it is necessary to plan the consumption pattern for clean water needs in lecture buildings, one of which is on the Sriwijaya State Polytechnic Teaching Industry campus. Considering the number of academics who will actively carry out activities on this campus, it is necessary to study the planning for clean water usage to obtain water consumption patterns. The research was carried out by taking samples of two buildings, namely buildings E I and E II which were planned as Workshop lecture buildings. Based on calculations and data analysis for planning clean water consumption patterns at the Sriwijaya State Polytechnic Teaching Factory campus, it is 7200 liters/day or 0.083 liters/second for Building E I and 7200 liters/day or 0.083 liters/second for Building E II.  The reservoir volume is planned with a capacity of 18 m3 and the tank volume with a capacity of 1 m3.